Entre dualidades e dualismos: a múltipla atuação de músicos e musicólogos em acervos musicais brasileiros - Amanda Pamela Santos Gomes (2018)
Brazilian musicology is often based on primary sources in documentary archives. These sources are the basis of academic and scientific texts. However, due to the precarious situation of the documentary collections, the research is not limited to the discovery of sources and critical study of these. Other aspects are also considered, such as documentary and informational management. In this context, a new researcher profile emerges: interdisciplinary musicologists. This generation is apparently more willing to develop a double research bias: study and promote document management (Janus Ofício).This dissertation aims to study this phenomenon in the Brazilian context, placing this practice in musicological studies, presenting the interdisciplinary nature of musicology and research in archives and determining an academic and professional profile of the researchers. Initially, I presented a report of research experience in the Archive Curt Lange-UFMG (2016-2017), highlighting the duality of performance, and the motivations for the development of this dissertation For this, structured the dissertation in three parts: 1) Literature review, on the relations between Musicology, documentary survey and management of musical collections, highlighting the complexity of Relational Musicology; 2) Relationship of interdependence observed by the Brazilian academic-scientific literature, (optimization of the national musicological research from the development of the musical archivology); 3) Conducting a research through the application and analysis of questionnaires, aiming to identify the professional academic profile of musicians and musicologists working in the context of the Janus Ofício in Brazil. This study demonstrated the main characteristics of the musicological formation of the collaborators, considering this dual performance as dimensions of the same complexity.